Beyond reason: revising the place of literature in theories of the uncanny - Anderson, Wesley (Department of English Language and Literature, 2017)
The psychoanalytic fixation in seeking to validate 'the real' has long overlooked various key components in theories of the uncanny as they relate to literature. The goal of the present study is to reaffirm the roles of uncertainty, ambiguity, and the purposeful lack of closure in the experience of the uncanny, features which will come to form an integral part of a new theory.